(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2019)
The method of diverse (multifaceted) actualization in the aphoristic text is comprehended in the article. Attention is drown to the problem questions of the modern aphoristic in common and determination of aphorism status. Discussion character of the main linguistic parameters of the aphorism is submitted in the paper. There are interpretation and separating of the categorical features, clarification of semantic, communicative, pragmatic, ethno-cultural peculiarities etc. Traditional terms such as “aphorism”, “aphoristic unit”, “aphoristic expression” and terms like “aphoristic genre”, “aphoristic style”, “aphoristic text”, “aphoristic discourse” are represented. Trying to expand research aspects of the aphorisms from the linguistic text position is demonstrated in the article. The approaches to definition “aphoristic text” are found. These approaches are based on the specific interaction of content and expression; the presence of the main elements of communicative situation (sender → text → receiver). The present paper concentrates on searching the original mechanism of actualization intertextual communications and system relationships for realization of pragmatic aim and reaching of cognitive-emotion effect. Such searching is connected with actualization like realization of the potential attributes of language elements in the speech. The article is manifested lack of coordination in the definition concept of “actualization” in general and “double actualization” in particular. The last is belonged mostly to the area of phraseology units’ functioning. Aphorism authors use actualized linguistic means and usual (automatic) means in unusual (de-automatic) context surround, they unbalance the system of linguistic means for achievement of the communicative-pragmatic effect. Described unbalance happens in different ways, with using various linguistic-stylistic devices, among which so-called diverse or multifaceted actualization is distinguished. Diverse actualization is interpreted as individually author’s method of organization of the expression plan, as choice and contamination of automatic linguistic means that manifest different (explicit and implicit) meanings (content aspect) in the same context circumstance. It in turn helps to create the effect of attractiveness, arouses an interest and a delight and opens interesting interpretation possibilities. Special attention is paid to fact that usus linguistic means, which are attracted in the production process, manifest different level of the tension, the information saturation. But capable contamination of them within some aphorism certify appearance of “maximum intensity”, that is based on interaction of literal and figurative, primary and secondary, denotative and connotative, free and bound senses etc.